Non-timber forest Products of Jaldapara Wildlife Sanctuary: an Assessment - Pandlt, P. K.; Ghosh, Chandra; Das, A. P. (Indian Forester, 2004)
Jaldapara Wildlife Sanctuary has been surveyed for the availability of type and amount of Non-Timber Forest Produces. A total of 132 species has been recognised as NTFP producers which include plants of different habit groups, occupying different strata and types of vegetation. While the existence of an established market for only 22 of these articles are there a list of another 27 articles have been provided for which proper markets need to be developed immediately. Prices for at least 33 articles could not be ascertained. Stress has provided for the proper survey of NTFPs in North Bengal vegetations and to develop strategies for their proper sustainable extraction and utilisation.